Coupling the State and Contents of Consciousness - Aru, Jaan; Suzuki, Mototaka; Rutiku, Renate; Larkum, Matthew E.; Bachmann, Talis (Frontiers in Systems Neuroscience, 2019)
One fundamental feature of consciousness is that the contents of consciousness depend on the state of consciousness. Here we propose an answer to why this is so: both the state and the contents of consciousness depend on the activity of cortical layer 5 pyramidal neurons. These neurons affect both cortical and thalamic processing, hence coupling the cortico-cortical and thalamo-cortical loops with each other. Functionally this coupling corresponds to the coupling between the state and the contents of consciousness. Together the cortico-cortical and thalamo-cortical loops form a thalamo-cortical broadcasting system, where the layer 5 pyramidal cells are the central elements. This perspective makes one quite specific prediction: cortical processing that does not include layer 5 pyramidal neurons will be unconscious. More generally, the present perspective suggests that layer 5 pyramidal neurons have a central role in the mechanisms underlying consciousness.